Cluster as a Tool to Increase the Competitiveness and Innovative Activity of Enterprises of the Defense Industry Complex - Katrina B. Dobrova (Модернизация, инновация, развитие, 2017)
Purpose: the main goal of the publication is to make a comprehensive study of the possible application of the cluster approach to improve the competitiveness and innovation activity of enterprises of the defense industry complex.Methods: the methodology of the research is based on the collection and analysis of initial data and information, the article uses a systematic approach to the study of socio-economic processes and phenomena. The research is based on modern theory of competition, innovation, as well as the modern paradigm of cluster development of the economy. In preparing the study, practical materials from Corporation “Rostec”.Results: the article gives the notion of cluster, the prospects for the use of the cluster approach to enhance competitiveness and innovation enterprises of the military-industrial complex. It is noted that the activation of interaction with the “civil sector” is particularly relevant in the context of the reduction of the state defense order, and the theory and practice of cluster management offers a number of forms of cluster interaction between the enterprises of the defense industry and the civil sector. It is emphasized that the development of cluster mechanisms can solve a number of problems related to the insufficient financial stability of defense industry enterprises in the context of a reduction in the state defense order, low innovation activity and the lack of developed models of interaction with small innovative enterprises. Ultimately, the use of cluster mechanisms in the development of defense enterprises is intended to enhance the competitiveness of the complex, both nationally and globally. It is stated that the existing clusters are not able to fully solve a number of specific tasks related to the diversification of integrated defense industry structures. Attention is drawn to the fact that existing clusters are not able to fully solve a number of specific tasks related to the diversification of integrated defense industry structures, such as the need to use information constituting state secrets, interaction with military representatives, various military state standards, special terminology. Recommendations are given on the activation of the potential of clusters with the participation of defense enterprises, for which it is proposed to initiate, in the established procedure, procedures for amending the legislation regulating industrial policy issues, to form additional organizational, legal and financial-economic preconditions for the cluster development of the military-industrial complex.Conclusions and Relevance: conclusion is drawn that the development of clusters based on the defense industry enterprises can be used, first of all, to diversify production and increase the output of civil high-tech products. To activate the cluster mechanism it is recommended to form additional organizational, legal and financial-economic prerequisites.